Transformasi Digital, Inovasi, Kinerja, Kebijakan sebagai Upaya Ketahanan UKM : Analisis Bibliometrik - Putri, Aulia Utami; Mirani, Dwi; Khairunnisyah, Tuty (Jurnal Pemerintahan dan Politik, 2024)
SME resilience can be overcome with digital transformation supported by policies and collaboration between government, industry, and SMEs. To gain an understanding of digital transformation and innovation, the study conducted a thorough bibliometric analysis. Use of bibliometric visualization software, Publish or Pelish, and VOSviewer. The results show that digital transformation, innovation, performance, and policies are critical to SME resilience. The digital transformation of SMEs has a crucial role in shaping policies, improving public services, shaping more open political dynamics, and encouraging more effective collaboration between the government and various stakeholders. The study also identifies new topics such as enterprises, digital technologies, digital transformation strategies, empirical evidence, industry, innovation, and policy that require further research. These results provide policymakers, businesses, and researchers with valuable insights into how to face challenges and seize opportunities to maintain SME resilience.